2015
DOI: 10.1039/c5ob00695c
|View full text |Cite
|
Sign up to set email alerts
|

Glycosmisines A and B: isolation of two new carbazole–indole-type dimeric alkaloids from Glycosmis pentaphylla and an evaluation of their antiproliferative activities

Abstract: Two unique carbazole-indole-type dimeric alkaloids, glycosmisines A (1) and B (2), have been isolated from the stems of Glycosmis pentaphylla and their structures are elucidated by 1D and 2D NMR analyses, and their cytotoxicity against the growth of three cancer cell lines (A549, HepG-2 and Huh-7 cells) in culture was investigated using an MTT assay. Compounds 1 and 2 exhibited significant levels of cytotoxicity against three human cancer cell lines, and these two compounds also induced apoptosis in the same c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…A naphthoquinone, glycoquinone ( 219 ) and acridone alkaloid, glycocitrine-III ( 220 ) (Figure 16) [152], four hydroquinone diglycoside acyl esters, glypentosides A–C ( 221 – 223 ) and seguinoside F ( 224 ) [153], carbazole alkaloid, 4-(7-hydroxy-3-methoxy-6-methyl-9 H -carbazol-4-yl)but-3-en-2-one ( 225 ), two dimeric carbazole alkaloids, bisglybomine B ( 226 ) and biscarbalexine A ( 227 ), together with glybomine B, glycoborinine, carbalexine A, 4,8-dimethoxy-1-methyl-3-(3-methylbut-2-en-1-yl)-quinolin-2(1 H )-one, 4,8-dimethoxyfuro [2,3- b ]quinoline, skimmianine and arborinine [154], three phenolic glycosides, glycopentosides D–F ( 228 – 230 ) [155] and two carbazole indole-type dimeric alkaloids, glycosmisines A ( 231 ) and B ( 232 ) [156] were isolated from the stems of G. pentalphylla . Alkaloid, glycophymine ( 233 ) and an amide, glycomide from the flowers of this species [157] and derivative of carbazole alkaloid, glycozolinine ( 234 ) was identified from the seeds of G. pentaphylla [158].…”
Section: Phytochemistry Medicinal Properties and Ethnopharmacologmentioning
confidence: 99%
See 1 more Smart Citation
“…A naphthoquinone, glycoquinone ( 219 ) and acridone alkaloid, glycocitrine-III ( 220 ) (Figure 16) [152], four hydroquinone diglycoside acyl esters, glypentosides A–C ( 221 – 223 ) and seguinoside F ( 224 ) [153], carbazole alkaloid, 4-(7-hydroxy-3-methoxy-6-methyl-9 H -carbazol-4-yl)but-3-en-2-one ( 225 ), two dimeric carbazole alkaloids, bisglybomine B ( 226 ) and biscarbalexine A ( 227 ), together with glybomine B, glycoborinine, carbalexine A, 4,8-dimethoxy-1-methyl-3-(3-methylbut-2-en-1-yl)-quinolin-2(1 H )-one, 4,8-dimethoxyfuro [2,3- b ]quinoline, skimmianine and arborinine [154], three phenolic glycosides, glycopentosides D–F ( 228 – 230 ) [155] and two carbazole indole-type dimeric alkaloids, glycosmisines A ( 231 ) and B ( 232 ) [156] were isolated from the stems of G. pentalphylla . Alkaloid, glycophymine ( 233 ) and an amide, glycomide from the flowers of this species [157] and derivative of carbazole alkaloid, glycozolinine ( 234 ) was identified from the seeds of G. pentaphylla [158].…”
Section: Phytochemistry Medicinal Properties and Ethnopharmacologmentioning
confidence: 99%
“…Streejith et al, reported in 2012 the anti-hepatocellular carcinoma cell line activity of G. pentaphylla ethanol extract in reducing the proliferation of Hep3 B cells [151]. Biscarbalexine A ( 227 ), glycosmisines A ( 231 ) and B ( 232 ) displayed significant the cytotoxic activity against human cancer A549, HepG-2 and Hun-7 cell lines, showing with an IC 50 values of 56.05, 43.68 and 57.01 μM for A549 cell line, 60.06, 50.30 and 62.89 μM for HepG-2 cell line and 73.16, 30.60 and 62.87 μM for Huh-7 cell line, respectively [156]. G. pentaphylla ethanolic crude extract showed a significant antioxidant activity [169].…”
Section: Phytochemistry Medicinal Properties and Ethnopharmacologmentioning
confidence: 99%
“…Stems of Glycosmis pentaphylla afforded glycosmisines A ( 605 ) and B ( 606 ), two unique alkaloids dimeric from a carbazole unit and a indole unit (Chen et al, 2015c ). Three rearranged labdane-type diterpenoids, hapmnioides A–C ( 607 – 609 ), were obtained from Haplomitrium mnioides (Guizhou, China) (Zhou et al, 2016c ), Two unprecedented labdane-type diterpenoids with a six-rings' system, haplomintrins A ( 610 ) and B ( 611 ), were also obtained from Haplomitrium mnioides (Zhou et al, 2015b ).…”
Section: Terrestrial Plantsmentioning
confidence: 99%
“…[5][6][7] Recently, Garmultin A is a polycyclic caged acylphloroglucinol isolated from the leaves and twigs of G. multiora, which been highlighted in Hot off the Press articles in Natural Product Reports. 8,9 In the continuing search for antitumor natural products, 10,11 a new regioisomeric pair of garcimultine A (1) and B (2), one new tocotrienol derivative garcimultine C (8), together with six known compounds were isolated from the fruits of G. multiora. Herein, we report the isolation, structural elucidation, and biological activities of these isolated compounds.…”
Section: Introductionmentioning
confidence: 99%